Correlation of High BMI and Hyperlipidemia with Myocardial Ischemia - Imran Ali Zaidi, Haleema Sajid, Sobia Niaz, Shamaila Doggar, Farouk Qamar Malik, Sana Hafeez, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Myocardial ischemia is considered as one of most common cause of mortality worldwide. Several Risk factors are linked to an increased incidence of Myocardial Ischemia. The most common risk factors are hypertension, hypercholesterolemia, diabetes mellitus, high BMI, physical inactivity, smoking, age and gender predisposition and socioeconomic status. Aim: To inspect and compare incidence of myocardial ischemia in cases with hyperlipidemia and elevated BMI. Methods: 102 patients were selected for our research study and cases were split up into 2 groups of 51 patients each. Group A comprised cases with standard normal lipid profile and BMI with suspected myocardial ischemia. Group B contained 51 patients with hyperlipidemia and high BMI with suspected myocardial ischemia. The study data was then analyzed by SPSS 21st version. The Probability Value (P- Value) of ≤0.05 was coined as statistically convincing value. Results: The serum Cholesterol levels were 148 ± 11 in first group A and 268 ± 41 in other group B. The triglycerides serum values were 129± 13 in A group and 220± 13 in B group. The serum Low density Lipoproteins values were 109±10 in A group and 179±22 in B group. The serum HDL values were 39±10 in A group and 20±08 in B group. An independent/unpaired samples T- statistical test was used Using a two-tailed 0.05 criterion, the test indicated a statistically convincing difference among the two research groups (p value was <0.05) in relation to cholesterol, triglycerides, HDL, LDL and BMI. Conclusion: Hyperlipidemia and High BMI contribute significantly to development of acute myocardial ischemia Keywords: Myocardial Ischemia, Hyperlipidemia, Body Mass index